In situ Diamond Anvil Cell–Raman Spectroscopy and Nanoindentation Study of the Pressure‐Induced Phase Transformation in Pure and Zinc‐Doped β‐Eucryptite. Issue 6 (28th February 2013) - Ramalingam, Subramanian; Packard, Corinne E.; Reimanis, Ivar E.; Pharr, G.
<x xml:space="preserve">Abstract</x> β‐eucryptite (LiAlSiO4), a member of the family of lithium aluminum silicates, is known to undergo a reversible pressure‐induced phase transformation at 0.8 GPa to ε‐eucryptite. This study correlates the results between two techniques, in situ diamond anvil cell–Raman spectroscopy and nanoindentation experiments, to explore how doping (substituting Zn for Li) influences this pressure‐induced phase transformation. Diamond anvil cell tests carried up to 3 GPa hydrostatic stress under Raman spectroscopy were compared with nanoindentation results, which provide a more localized, multiaxial stress state. The results indicate that the magnitude of hysteresis observed (difference between the pressures required for the forward and reverse transformation) is lower for Zn‐doped β‐eucryptite; however, the onset of the phase transformation is unchanged by doping with Zn. Furthermore, calculations of activation volume from nanoindentation experiments yield similar values ( 0.1 nm3) for pure and Zn‐doped β‐eucryptite, suggesting that the nucleation event that establishes the onset of the phase transformation is the same for both materials.